2013
DOI: 10.1093/nar/gkt603
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PA-N terminal domain of Influenza A polymerase reveals sequence specific RNA cleavage

Abstract: Influenza virus uses a unique cap-snatching mechanism characterized by hijacking and cleavage of host capped pre-mRNAs, resulting in short capped RNAs, which are used as primers for viral mRNA synthesis. The PA subunit of influenza polymerase carries the endonuclease activity that catalyzes the host mRNA cleavage reaction. Here, we show that PA is a sequence selective endonuclease with distinct preference to cleave at the 3′ end of a guanine (G) base in RNA. The G specificity is exhibited by the native influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
71
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 29 publications
6
71
3
Order By: Relevance
“…On the contrary, we noted a 6-times higher V max with MB-U 6 A 2 U 7 -DFO than with MB-het2-DFO. This contrasts with the observation by another group that PA-Nter has a preference for 59-GC-39 in RNA substrates (Datta et al, 2013). However, efficient cleavage of U-rich RNA substrates was already demonstrated by Dias et al (2009).…”
Section: +contrasting
confidence: 84%
See 2 more Smart Citations
“…On the contrary, we noted a 6-times higher V max with MB-U 6 A 2 U 7 -DFO than with MB-het2-DFO. This contrasts with the observation by another group that PA-Nter has a preference for 59-GC-39 in RNA substrates (Datta et al, 2013). However, efficient cleavage of U-rich RNA substrates was already demonstrated by Dias et al (2009).…”
Section: +contrasting
confidence: 84%
“…1). Among the various PA-Nter substrates that were reported to work (Dias et al, 2009;DuBois et al, 2012;Kowalinski et al, 2012;Parhi et al, 2013;Bauman et al, 2013;Datta et al, 2013;Chen et al, 2014), we chose the M13mp18 single-stranded DNA plasmid since it is commercially available. The active site substitution K134A in the PA-Nter enzyme completely abolished the endonucleolytic cleavage, in agreement with previous reports (Hara et al, 2006;Yuan et al, 2009;Crépin et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Translation of viral mRNAs by the host ribosome requires that they be 5′ capped, and this is achieved in cells infected with influenza virus by a "cap-snatching" mechanism in which the endonuclease cleaves 5′ caps from host mRNAs, which then act as transcription primers (19). The endonuclease domain occupies the N-terminal half of PA (PA N ) (20,21) and contains a two-metal (Mn 2+ ) active site that preferentially cleaves the pre-mRNA substrate at the 3′ end of a guanine located 12 nucleotides from the 5′ cap (22). The active site is well conserved (23), and crystal structures have revealed how it…”
mentioning
confidence: 99%
“…PB1 binds to the C-terminal domain of PA (14,15), while the N-terminal domain of PA (PAn) can function as an endonuclease to generate small RNA primers that are essential for initiation of the viral gene transcription (16,17). Recently, it has been shown that both PAn (18) and full-length PA (19) cleave the host-derived RNA in a sequence-specific manner.…”
mentioning
confidence: 99%